Evaluation of the allelopathic potential of fifteen common Malaysian weeds - Nurul Ain M.B.; Nornasuha Y.; Ismail Sahid (Penerbit Universiti Kebangsaan Malaysia, 2017)
The use of allelopathy concept in weed management has received attentions to minimize extensively the reliance on herbicide applications on the agriculture industry in Malaysia. A laboratory study was conducted to evaluate the allelopathic potential of 15 Malaysian common weed species of different morphological characteristics (broadleaves, sedges and grasses). They were screened using the Sandwich method (from leaf litter leachate) and the Dish pack method (for testing the presence and content of volatile compounds in weeds). Among the 15 weed species tested, the leaf litter leachate of Centrosema pubescens was observed to be the most sensitive plant material inhibiting the growth of lettuce radicle (84%) and hypocotyl (55%) in the Sandwich bioassay compared to the control. This was followed by Asystasia gangentica (81%) and Cynodon dactylon (80%) inhibiting the lettuce radicle growth. In the Dish pack bioassay, Rhynchelytrum repens demonstrated maximum inhibition on the radicle and hypocotyl elongations by 44% and 29%, respectively, (over control) at 41 mm distance from the source well. Meanwhile, at the same distance, Cynodon dactylon was observed to have the least inhibitory effect on lettuce radicle growth by 12%. The results presented can be utilized as benchmark information for further research on the identification and isolation of allelochemicals for weed control strategies.